PERLINDUNGAN PENGGUNA E-COMMERCE AGAR TETAP AMAN BERTRANSAKSI DI KIOSDELIMA.COM - Artika Surniandari (Cakrawala - Jurnal Humaniora, 2015)
The development of information technology brings us increasingly dependent on this single facility with the convenience offered on an application made on the basis of the internet. E-commerce is one of them by doing transactions online shoppers and buyers met regardless of distance and time, because through e-commerce transactions can be done at any time. With the research methods described desfriptif Actual condition of the object under study as to which takes place when the research is done. It turns out that the convenience offered is often misused by people who are not responsible and can certainly cause harm to other users. For why should the users of e-commerce know what rights and obligations they have to do when trading using this facility.Keywords : Perlindungan Konsumen, E-Commerce